GAMBARAN PRAKTIK ANAK DALAM PENCEGAHAN KARIES GIGI DENGAN KEJADIAN EARLY CHILDHOOD CARIES (ECC) PADA ANAK PRASEKOLAH DI WILAYAH KERJA PUSKESMAS BANDARHARJO, SEMARANG UTARA, KOTA SEMARANG - Raras Sekti Pudyasari; Henry Setyawan Susanto; Retno Hestiningsih; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dental caries is a dental damage which characterized by demineralization of dental hard tissues followed by organic material damaged. Dental caries is one of the dental and oral diseases that common in community, including groups of children. The prevalence of dental caries of children under 12 years in Indonesia in 2013 is 89%. The purpose of this study is to analyze children practice in the prevention of dental caries with Early Childhood Caries (ECC) in preschool children in the work area of Bandarharjo Public Health Center. The type of research is analytic observational research with cross sectional design. The population in this study is preschool children with total of 1344 children, while the sample is taken as many as 158 children using multistage random sampling method. The Primary data was obtained by interviewing on child, the examination of dental caries, and observation of the practice of brushing teeth. The result shows that there are 137 preschool children (86,7%) have dental caries with the def-t index in the number of 7,63 that is included as very high category. The results of bivariate analysis with Rank Spearman test show that there is a relation children practice (p=0,000; rho=-0,710; POR=2,6) with the incidence of dental caries in preschool children. It is suggested for parents to accompany their children for brushing with the correct method after eating and before sleeping, to reduce cariogenic consumption and take routine control to the dentist. It is important for Bandarharjo Public Health Center to increase dental and oral health program in its working area.